A systematic review investigating measurement properties of physiological tests in rugby - Matthew Chiwaridzo; Sander Oorschot; Jermaine M. Dambi; Gillian D. Ferguson; Emmanuel Bonney; Tapfuma Mudawarima; Cathrine Tadyanemhandu; Bouwien C. M. Smits-Engelsman (BMC, 2017)
Abstract Background This systematic review was conducted with the first objective aimed at providing an overview of the physiological characteristics commonly evaluated in rugby and the corresponding tests used to measure each construct. Secondly, the measurement properties of all identified tests per physiological construct were evaluated with the ultimate purpose of identifying tests with strongest level of evidence per construct. Methods The review was conducted in two stages. In all stages, electronic databases of EBSCOhost, Medline and Scopus were searched for full-text articles. Stage 1 included studies examining physiological characteristics in rugby. Stage 2 included studies evaluating measurement properties of all tests identified in Stage 1 either in rugby or related sports such as Australian Rules football and Soccer. Two independent reviewers screened relevant articles from titles and abstracts for both stages. Results Seventy studies met the inclusion criteria for Stage 1. The studies described 63 tests assessing speed (8), agility/change of direction speed (7), upper-body muscular endurance (8), upper-body muscular power (6), upper-body muscular strength (5), anaerobic endurance (4), maximal aerobic power (4), lower-body muscular power (3), prolonged high-intensity intermittent running ability/endurance (5), lower-body muscular strength (5), repeated high-intensity exercise performance (3), repeated-sprint ability (2), repeated-effort ability (1), maximal aerobic speed (1) and abdominal endurance (1). Stage 2 identified 20 studies describing measurement properties of 21 different tests. Only moderate evidence was found for the reliability of the 30-15 Intermittent Fitness. There was limited evidence found for the reliability and/or validity of 5 m, 10 m, 20 m speed tests, 505 test, modified 505 test, L run test, Sergeant Jump test and bench press repetitions-to-fatigue tests. There was no information from high-quality studies on the measurement properties of all the other tests identified in stage 1. Conclusion A number of physiological characteristics are evaluated in rugby. Each physiological construct has multiple tests for measurement. However, there is paucity of information on measurement properties from high-quality studies for the tests. This raises questions about the usefulness and applicability of these tests in rugby and creates a need for high-quality future studies evaluating measurement properties of these physiological tests. Trial registrations PROSPERO CRD 42015029747 .